(untitled) (Sociedade e Estado, 2014)
Resenha sobre a obra: (Prévost, Jean-Guy; Beaud, Jean-Pierre. Statistics, public debate and the State, 1800- 1945: a social, political and intellectual history of numbers. London: Pickering and Chatto, 2012, 235 p.)